THE INFLUENCE OF SERUM LDL-CHOLESTEROL AND HDLCHOLESTEROL ON SYSTOLIC BLOOD PRESSURE OF TYPE II DIABETIC PATIENTS WITH VARIOUS KIDNEYS FUNCTION NOT YET ON DIALYSIS - Nasri, Hamid (Pakistan Journal of Physiology, 2006)
Background: This study was undertaken to elucidate whether and how in patients with type II diabetes the serum lipid concentrations affect the blood pressure of the patients. Methods: Blood pressure (BP) of the patients were measured. For patients glycosylated hemoglobin (HbA1c ) and serum lipids consisting of Triglycerides, cholesterol, High density lipoproteinwere measured using standard methods. Serum LDL-was calculated. Results: The present study included 122 patients (f=82, m=40). The mean patient's age was 63 (±10) years. The mean length of the time they were diabetic was 7.4 (±5.8) years (median: 6 years). The duration of hypertension was 3.2 (±4.6) years (median: 96 months). The mean serum LDL-chol was 112(±37) mg/dl (median: 112 mg/dl). The mean serum HDL-c was 47(±18) mg/dl (median: 44 mg/dl) .In this study a significant inverse correlation of serum HDL with mean systolic BP.In this study also a significant positive correlation of serum LDL-c with mean systolic BP was found too. Conclusion: This study has important implications for the increased susceptibility to vascular disease associated with LDL-c in diabetic patients. Hence, higher plasma concentrations of LDL-c though with in the normal range, could be an independent risk factor for developing hypertension or its aggravation. This study addressed the hypothesis the new therapeutic methods like statin groups may be identified to reduce LDL-C levels, which may prove to be useful in diabetic patients even in earlier onset of type II diabetes .